CREATING HALAL PRODUCTS FOR THE REALIZATION OF WAHDATUL ULUM SUPPLY CHAIN MANAGEMENT IN INDONESIA - Irma Septria Mawarni; Fernanda Putri; Siti Aisyah (Transpublika Publisher, 2022)
According to Imam Ghazali there are three aspects of wahdatul ulum including axiology, epistemology and ontology. The halal chain is one thing that must be used as a benchmark for Muslims in consuming various forms of food outside. There are various kinds of reviews that are used as benchmarks so that the food that can be consumed is halal food. This study aims to critically and deeply analyze the implementation of Wahdatul ulum's SCM or Supply Chain Management in Indonesia to create halal products. The writing of this journal is based on a type of qualitative research using a literature review approach. Halal products created based on SCM (Supply Chain Management) Wahdatul ulum are company products that are allowed to be consumed by Muslims. Wahdatul ulum is a unity of knowledge between general science and religious science. According to Imam Ghazali there are three aspects of wahdatul ulum including axiology, epistemology and ontology.